Field notes contributed by James L. Hansen, fall 1987 - Hansen, James L.et al (1987)
Fall report of birds found in northern Iowa contributed by James L. Hansen. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1987. Epson - sheet feed